Determinants of male participation in reproductive healthcare services: a cross-sectional study - Shahjahan, Md (BioMed Central, 2013)
BACKGROUND: The role of male’s participation in reproductive healthcare is now well-recognized. The present study investigated the role of men in some selected reproductive health issues, characterizing their involvement, including factors influencing their participation in reproductive healthcare services. METHODS: This study was conducted in the working areas of urban and rural implemented by NGOs. The sample-size was determined scientifically. The systematic sampling procedure was used for selecting the sample. The study included 615 men aged 25-45 years. Bivariate analysis was performed between male’s involvement as the dependent variable with several independent variables. Logistic regression analysis was applied to assess the effects of risk factors on the participation of men in reproductive health care services. RESULTS: The mean age of the respondents was little over 34 years while their mean years of schooling was 3.7, and their mean monthly income was about Tk 3,400 (US$ 1 = Tk 70) at the time of the study. Rickshaw-pulling and driving was the main occupation of the respondents from the urban while farming were main occupation in the rural area respectively. About two-thirds of the respondents discussed reproductive health issues with their wives and accompanied them to healthcare facilities. The current contraceptive-use rate was 63% among the men who attended the evening clinics. Results of bivariate analysis showed a significant association with education, occupation, income, access to media, and number of living children. Results of logistic regression analysis showed that secondary to higher education level, number of living children, paid employment status, long marital duration, and access to media were important correlates of males’ involvement in reproductive healthcare services. CONCLUSIONS: The results imply that a greater integration of reproductive healthcare matters with the Millennium Development Goals and increasing perception of men through enrollment in various components of reproductive activities will produce synergistic effects.